THE RACISM OF OTHERS: A POLEMIC ON DISCURSIVE SOCIAL PSYCHOLOGY AND ITS POLITICS - Painter, Desmond (PINS-Psychology in Society, 2026)
In this article I argue, through a series of reflections on nationalism, globalization, liberalism and the social sciences, that racism, especially a reflexive form of racism that is theoretically transposed onto the "cultural Other’s" resistance or indifference to liberal political imaginaries, provides ideological support for the often severely compromised universals of nationalism and globalization. The inverted logic of reflexive racism affects not only the political traditions of Modernity and the contemporary discourses of South African nation building, it also severely limits the critical ability of the social sciences to engage with its own endorsement of the normative "we" of liberal discourse. Relating this to discursive social psychology, I argue for a more explicit engagement with notions of the political.